Gracefulness of five permutation graphs of paths - Liang, Zhihe; Zhang, Huizhu; Xu, Na; Ye, Shuyan; Fan, Yanpeng; Ge, Hongmei (Utilitas Mathematica, 2007)
For any integer n > 1, the permutation graphs P(Pn, f) are graceful when f=(12345), (2345), (234), (123456) and (23) (45).